Reflections on Ijtihad and Moderate Islam (American Journal of Islam and Society, 2005)
My remarks focus on two central themes addressed in the preceding debate:moderate Muslim and ijtihad. Although my assignment requires me toengage the five illustrious interlocutors, I have chosen to refer to salientaspects of their statements, particularly those that help in clarifying the twothemes alluded to above. Given the brevity of my remarks and the limitedspace allocated to comments, it is not possible to expound on the epistemologicaland ontological underpinnings of the arguments. The followingarguments, therefore, take the form of a number of assertions that lack theoreticalgrounding. This will be felt particularly by readers who do notshare the basic assumptions upon which the arguments are premised. But,I guess this is exactly what the editor has intended: to explore diverse viewswithin and without the Muslim community.Still, this intellectual exercise provides an important backdrop for thecurrent debate about the significance of Islam in the profound transformationsoccurring in contemporary Islamic thinking. I also believe that thedebate reveals the complexity of the process of Islamic reform and diversityof its forms and manifestations.Moderate Islam“Moderate Islam” has become a most contentious term, as the debate aboveshows. The word moderate is frequently used in reference to the politicalcentrist: “A person who takes a position in the political center.” Amoderateis a person who is neither on the extreme left nor on the extreme right ofthe political, moral, or religious spectrum of ideas.Defining moderate becomes tricky when one takes a historical view ofmainstream society. From a historical point of view, the terms moderateand extremist immediately loose their absolutist standing and acquire a ...